Green method, optical and structural characterization of zno nanoparticles synthesized using leaves extract of m. Oleifera - González-Fernández J.V. (2022)
Funding Statement: Authors are grateful to Concytec-Peru and The World Bank for the financial support of this project under the call “Mejoramiento y Ampliación de los Servicios del Sistema Nacional de Ciencia Tecnología e Innovación Tecnológica” 8682-PE, through Fondecyt Grant 017-2019 FONDECYT BM INC.INV.